A finite-element heat transfer model for orthogonal cutting. Issue 4 (1st October 2020) - Kumar, Ankit; Bhardwaj, Rajneesh; Joshi, Suhas S.
ABSTRACT: It is known that the heat generated in various cutting zones during machining affects the formation of chips, the shearing mechanism, the chip-tool friction and consequently the tool wear and tool life. Therefore, determining the temperature distribution in machining is a major area of research. In the past, numerical approaches have been used by researchers which involved use of stationery heat sources to predict temperature distributions around the cutting zone in machining. This work presents a thermal model of orthogonal machining process to evaluate the temperature distribution in the work, tool and chip-tool interface. A series of numerical simulations were performed using finite element method (FEM) solver to develop a steady-state two-dimensional heat transfer model considering heat convection due to coolant applications in variety of cutting zones. The maximum temperature generated during machining has been validated using the numerical as well as experimental data. The simulations successfully captured the maximum temperature generated in machining of three different variants of Titanium alloys with an error of ~9%.